Incredibles 2 [videorecording (DVD)] - Bird, Brad, 1957-; Bird, Brad, 1957- ([publisher not identified], 2018)
When Helen is chosen to lead a mission to help the public regain trust in superheroes, Bob is left at home, struggling in his new role as a stay-at-home parent.